Hakîkat Yolcusunun Son Durağı: Nifferî’ye Göre Vakfe / The Final Destination of the Truth Seeker: Waqfah According to Al-Niffarî - Yıldız, Mehmet (Journal of History Culture and Art Research, 2017)
Abstract This study examines Islamic mysticism according to Abdu’l-Jabbar Al-Niffarî who has been accepted as an importing figure in Islamic mysticism and among the pioneers of Ibn Arabi in the history of Sufism. Niffarî, who lived in the fourth century (AH), couldn’t find much fame since he preferred a humble and individual life style. The recent academic researches have shed light on his deserved reputation. The first comprehensive study about Nifferî belongs to M. Mustafa Çakmaklıoğlu in Turkey, which I review in this paper. In this study, Çakmaklıoğlu intensely examines Niffarî’s life, works, and contribution to Sufi knowledge. The author tries to understand Niffarî, who uses a very vehement, dense, symbolic, and paradoxical language, through Ibn Arabi since he is familiar with his earlier works. Öz Bu çalışma Tasavvuf tarihinde İbn Arabî’nin öncülerinden kabul edilebilecek önemli bir sûfî olan Abdülcebbâr en-Nifferî’yi konu edinmektedir. Hicrî dördüncü asırda yaşayan Nifferî, yapı itibariyle münzevî ve münferit bir hayatı tercih ettiği için kendi döneminden itibaren Tasavvuf tarihinde pek şöhret bulmamıştır. Hak ettiği şöhreti ise yakın geçmişte kendisi üzerinde yapılan bilimsel çalışmalar sonucu elde etmiştir. Türkçe’de Nifferî hakkında yapılan ilk kapsamlı çalışma M. Mustafa ÇAKMAKLIOĞLU’na aittir. Çakmaklıoğlu bu çalışmasında Nifferî’nin hayatını, eserlerini ve Tasavvuf ilmine kazandırdığı vakfe, mevkıf kavramlarını derinlemesine işlemektedir. Yazar çok veciz, yoğun, sembolik, paradoksal bir dil kullanan Nifferî’yi daha önceki çalışmalarında aşina olduğu İbn Arabî üzerinden anlamaya çalışmaktadır.